2007
DOI: 10.1038/nature05621
|View full text |Cite
|
Sign up to set email alerts
|

Origin of avian genome size and structure in non-avian dinosaurs

Abstract: Avian genomes are small and streamlined compared with those of other amniotes by virtue of having fewer repetitive elements and less non-coding DNA. This condition has been suggested to represent a key adaptation for flight in birds, by reducing the metabolic costs associated with having large genome and cell sizes. However, the evolution of genome architecture in birds, or any other lineage, is difficult to study because genomic information is often absent for long-extinct relatives. Here we use a novel bayes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
310
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(325 citation statements)
references
References 25 publications
13
310
2
Order By: Relevance
“…This would place partially reduced genome sizes among other features such as bipedal locomotion, feathers and possibly endothermy that appeared prior to, but then became important in, the evolution of avian flight. However, just as feathers subsequently became specialized for flight in birds, the fact that the estimated mean genome size for theropod dinosaurs (Organ et al 2007) is notably larger than that for the average modern bird (Gregory 2008) implies that genome sizes continued to shrink along with specializations for flight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would place partially reduced genome sizes among other features such as bipedal locomotion, feathers and possibly endothermy that appeared prior to, but then became important in, the evolution of avian flight. However, just as feathers subsequently became specialized for flight in birds, the fact that the estimated mean genome size for theropod dinosaurs (Organ et al 2007) is notably larger than that for the average modern bird (Gregory 2008) implies that genome sizes continued to shrink along with specializations for flight.…”
Section: Discussionmentioning
confidence: 99%
“…New light has been recently shed on this issue by Organ et al (2007) who analysed the sizes of fossil osteocytes in dinosaurs and concluded that birds inherited already diminutive genomes from ancestral theropod dinosaurs (see also Ellegren 2007;Zimmer 2007). This would place partially reduced genome sizes among other features such as bipedal locomotion, feathers and possibly endothermy that appeared prior to, but then became important in, the evolution of avian flight.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that hovering flight and reduced genome size evolved in concert early in the hummingbird lineage. Further genome size estimates for owlet-nightjars and swifts and cell size estimates for fossil Apodiformes will bear on this hypothesis (Mayr 2004;Organ et al 2007;Organ & Shedlock 2009), but remain unavailable at present.…”
Section: Genome Sizes Of Hummingbirdsmentioning
confidence: 99%
“…Importantly, it has recently been shown that saurischian dinosaurs (from which birds are derived) had already undergone an initial reduction in genome size prior to the evolution of flight (Organ et al 2007), though their estimated genome sizes were larger than those of most modern birds. Moreover, genome sizes have been suggested to assort according to flight ability in extant birds, with strong fliers possessing the smallest genomes and flightless birds some of the largest (Hughes 1999;Gregory 2005).…”
Section: Introductionmentioning
confidence: 99%
“…People have asked how and why genomes vary so extensively and whether it matters. The recent paper by Organ et al (2007) has extended a paleogenomics dimension to these questions. By using the size of fossil dinosaur bone cells as proxies for genome size, they have attempted to trace the evolution of genome size in reptiles over 200 million years.…”
mentioning
confidence: 99%